1993
DOI: 10.1177/104063879300500311
|View full text |Cite
|
Sign up to set email alerts
|

Genus-Specific Detection of Salmonellae using the Polymerase Chain Reaction (PCR)

Abstract: Oligonucleotide primers for the polymerase chain reaction (PCR) that enable genus-specific detection of members of the genus Salmonella were developed. The primers amplify a 496-bp genetic sequence of members of the genus Salmonella. Amplification of DNA extracted from all other genera of the family Enterobacteriaceae and various other gram-positive aerobic and anaerobic bacteria yielded negative results. Applications of the PCR using these genus-specific primers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 9 publications
0
68
0
Order By: Relevance
“…Upper strand and Lower strand primer was used. 19 In the present study, it was found that the E. coli isolated from broiler were sensitive to ciprofloxacin and gentamicin. The results strengthen the earlier observations of some study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Upper strand and Lower strand primer was used. 19 In the present study, it was found that the E. coli isolated from broiler were sensitive to ciprofloxacin and gentamicin. The results strengthen the earlier observations of some study.…”
Section: Discussionmentioning
confidence: 79%
“…[15][16][17] Isolates of E. coli observed in EMB agar revealed smooth, circular, greenish black color colonies with metallic sheen and pink color colonies on McConkey agar. [18][19][20][21] In Gram's staining, the morphology of the isolated bacteria exhibited Gram-negative, short rod arranged in single or paired. 22,23 The Salmonella revealed smooth, circular, black centered colonies on XLD agar.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,21 The invA gene is the target of many of these methods because it not only is specific to the Salmonella genus, but it is also found in all known serovars of Salmonella.…”
Section: Introductionmentioning
confidence: 99%
“…The Histidine transport operon and JEO402-1 genes are reported as highly conserved regions in all Salmonella species [12,13]. The presence of these two genes in our study was distinctive of all four strains of Salmonella evaluated.…”
Section: Discussionmentioning
confidence: 55%
“…Primers with highly conserved regions to detect pathogenic Salmonella were selected from the literature: invA [10], fimC [11], JE0402-1 [12], and histidine operon transport [13]. The cocktail for the PCR reaction contained 4 µl of genomic DNA (100 ng/µl) obtained by heat shock treatment and 16 µl of the following solution: 5% Glycerol, 1.5 Mm MgCl2, 0.8 Mm dNTPs, 0.2 µM of each primer and 0, 05 U de Platinum Taq-polymerase (Invitrogen, United States).…”
Section: Pcr Detectionmentioning
confidence: 99%